b-a=d

Simple and best practice solution for b-a=d equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for b-a=d equation:


Simplifying
b + -1a = d

Reorder the terms:
-1a + b = d

Solving
-1a + b = d

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-1b' to each side of the equation.
-1a + b + -1b = -1b + d

Combine like terms: b + -1b = 0
-1a + 0 = -1b + d
-1a = -1b + d

Divide each side by '-1'.
a = b + -1d

Simplifying
a = b + -1d

See similar equations:

| p^3-3p+2=0 | | 18y+3y=6 | | s(4+p)=m | | X+3.2=7.5 | | 5(+4)=18-9 | | 3(4-6k)+1=-131 | | 3y+18y=6 | | 36x^2-48x+16=1 | | -5q-2(1-q)=-6q | | -2-1=-x-3 | | 3x+3x+15+2x+5=180 | | 6m+3=3m+3 | | 45b+2=-15b+3 | | h+9.1=5.3 | | 3+6=m | | 14x+7+20x+5=90 | | -3(6k+7)+6=93 | | 3(x+9)-2x+7=3(5x-8)-13x-7 | | 2x^2+8x+2y^2=0 | | 2(a-5-3)-5=3 | | 20+(-8x)-18=x | | -2x^2-3x+360=0 | | 6+x+6x=-22 | | 3x-5(2x+8)=9 | | 4x+3(x+2)=-17 | | x-31-(1.3x-31)=x | | 2t-11-8t=42 | | y-6=3(x-5) | | 2x^7-15x^5+12x^4=0 | | 3(-5)-y=1 | | 4x+10-3=10x+70-5 | | -13+7[x+4(x+1)]=x |

Equations solver categories